Preparation method and application of ultrathin buffer heat-resisting sheet based on polyimide foam material
By using a laminated structure of polyurethane/polyimide composite raw materials and red phosphorus/graphene aerogel and magnesium-aluminum hydrotalcite solution when combined with polyimide and aerogel material, pore blockage is avoided, thermal insulation performance and overall performance are improved, and the problem of degradation of thermal insulation performance in the prior art is solved.
Patent Information
- Application Number
- CN202411867265.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, when polyimide is combined with aerogel material, the polyimide will clog the pores of the aerogel, resulting in a degradation of the thermal insulation performance of the bonded material.
Polyurethane/polyimide composite raw materials are prepared by mixing the polyimide polyol raw materials with the polyurethane solution, and red phosphorus/graphene aerogel and magnesium aluminum hydrotalcite solutions are used as intermediate layers and secondary intermediate layers, and combined with the polyurethane/polyimide composite raw materials respectively to avoid clogging the aerogel pores.
The insulation ability of the heat insulation sheet is improved, and the problem of degradation of thermal insulation performance when polyimide is combined with aerogel material is solved, while enhancing the overall performance of the material.
Smart Images

Figure CN119684651A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyimide materials, and in particular to a preparation method and application of an ultra-thin buffer thermal insulation sheet based on polyimide foam material. Background Art
[0002] Polyimide is a type of high molecular polymer containing cyclic imide groups in the molecular chain. It has excellent mechanical properties such as high strength, high elastic modulus, wear resistance, and impact resistance. The glass transition temperature and melting point of polyimide are very high. It can work at very high temperatures and has good high temperature resistance.
[0003] Aerogel refers to a nanoscale porous solid material formed by the sol-gel method, in which gas replaces the liquid phase in the gel in a certain drying method. Aerogel has high specific surface area, high porosity, low density and excellent thermal insulation properties.
[0004] When polyimide is stacked and combined with aerogel materials, a material with high strength and heat resistance as well as good thermal insulation properties can be prepared. However, during the direct bonding process, polyimide will block the gaps in the aerogel material, affecting the porosity and specific surface area of the aerogel and reducing the thermal insulation properties of the combined material.
[0005] Therefore, it is necessary to improve the polyimide material to solve the above defects. Summary of the invention
[0006] The present invention overcomes the shortcomings of the prior art and provides a preparation method and application of an ultra-thin buffer thermal insulation sheet based on polyimide foam material, aiming to solve the defect in the prior art that the thermal insulation performance of the combined material is reduced when polyimide is combined with aerogel material.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing an ultra-thin buffer insulation sheet based on polyimide foam material, comprising the following steps:
[0008] S1: mixing a polyimide polyol raw material with a polyurethane solution, and performing a melt treatment to obtain a polyurethane / polyimide composite raw material;
[0009] S2: mixing red phosphorus and graphene oxide solution and heating them, and freeze-drying the obtained mixed solution to obtain red phosphorus / graphene aerogel;
[0010] S3: placing magnesium aluminum hydrotalcite powder in a glycine solution, soaking for 1-2 hours, taking out and drying to obtain substituted magnesium aluminum hydrotalcite powder, adding the substituted magnesium aluminum hydrotalcite powder and a silane coupling agent into 75% ethanol and mixing to obtain a hydrotalcite solution;
[0011] S4: The red phosphorus / graphene aerogel in S2 is used as an intermediate layer, the hydrotalcite solution in S3 is coated on the red phosphorus / graphene aerogel and dried to form a secondary intermediate layer, the polyurethane / polyimide composite material is placed on the secondary intermediate layer by ultrasonic spraying, and after drying, an ultra-thin buffer insulation sheet based on polyimide foam material is obtained.
[0012] In a preferred embodiment of the present invention, the solid content of the polyurethane solution in S1 is 30%-50%, and the isocyanate index of the polyurethane solution is 1.05-1.15.
[0013] In a preferred embodiment of the present invention, the mass ratio of the polyimide polyol raw material to the polyurethane solution in S1 is 1:1.5-2.0, the melting treatment temperature is 120-150° C., and the melting treatment time is 30-60 min.
[0014] In a preferred embodiment of the present invention, the concentration of the graphene oxide solution in S2 is 2-5 mg / mL, and the mass ratio of the red phosphorus to the graphene oxide solution is 1:5-10.
[0015] In a preferred embodiment of the present invention, the temperature for mixing and heating the red phosphorus and the graphene oxide solution in S2 is 80-100°C, the mixing and heating time is 30 minutes, and the freeze-drying process is: freezing at -50°C for 24-28 hours and then vacuum drying for 48-50 hours.
[0016] In a preferred embodiment of the present invention, the mass fraction of magnesium in the magnesium-aluminum hydrotalcite powder in S3 is 30-35%, the mass fraction of aluminum is 35-40%, the particle size of the magnesium-aluminum hydrotalcite powder is 5-20 μm, the concentration of the glycine solution is 1-2 mol / L, the immersion time is 1-2 h, and the silane coupling agent is one of KH-550 and KH-560.
[0017] In a preferred embodiment of the present invention, the drying condition in S3 is drying at 60-80° C. for 4-6 hours, and the mass ratio of the substituted magnesium aluminum hydrotalcite powder, the silane coupling agent and the 75% ethanol is 1:0.05-0.1:10-20.
[0018] In a preferred embodiment of the present invention, the ultrasonic spraying frequency in S4 is 20-40 kHz, and the polyurethane / polyimide composite raw material is dried at 80-100° C. for 4-8 hours.
[0019] In a preferred embodiment of the present invention, the mass ratio of the polyurethane / polyimide composite material, the hydrotalcite solution and the red phosphorus / graphene aerogel in S4 is 1:0.75-1.25:1.5-2.
[0020] In order to achieve the above-mentioned purpose, the second set of technical solutions adopted by the present invention is: an application of an ultra-thin buffer thermal insulation sheet based on polyimide foam material, wherein the ultra-thin buffer thermal insulation sheet is used to prepare a battery thermal insulation sheet.
[0021] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0022] (1) The present invention provides a method for preparing an ultra-thin buffer thermal insulation sheet based on a polyimide foam material, comprising mixing a polyimide polyol raw material with a polyurethane solution to prepare a polyurethane / polyimide composite raw material, mixing red phosphorus with a graphene oxide solution, heating and then freeze-drying to prepare a red phosphorus / graphene aerogel, placing magnesium aluminum hydrotalcite powder in a glycine solution for replacement to prepare a hydrotalcite solution, and sequentially combining the red phosphorus / graphene aerogel, the hydrotalcite solution and the polyurethane / polyimide composite raw material to prepare a thermal insulation sheet, which can be combined with polyurethane / polyimide and red phosphorus / graphene aerogel respectively through the groups on the hydrotalcite while avoiding affecting the pore structures of the two. Compared with the polyimide material in the prior art, it can be connected with polyurethane / polyimide and red phosphorus / graphene aerogel respectively through chemical bond connection, avoiding entering the pores of the aerogel and clogging the aerogel, thereby solving the defect of the prior art that the thermal insulation performance of the combined material is reduced when the polyimide and aerogel materials are combined.
[0023] (2) In the present invention, magnesium aluminum hydrotalcite powder is placed in a glycine solution, dried to obtain substituted magnesium aluminum hydrotalcite powder, and configured into a hydrotalcite solution. The magnesium aluminum hydrotalcite has good flame retardant and filling properties. The immersion and replacement treatment in the glycine solution helps to improve its dispersibility and bonding ability with the substrate. Compared with the prior art, it can provide bonding conditions for the combination of red phosphorus / graphene aerogel and polyurethane / polyimide composite raw materials and can reduce the blockage of pores, thereby improving the thermal insulation capacity of the thermal insulation sheet.
[0024] (3) In the present invention, red phosphorus / graphene aerogel is used as an intermediate layer, a hydrotalcite solution is coated on the red phosphorus / graphene aerogel to form a secondary intermediate layer, and a polyurethane / polyimide composite material is sprayed on the secondary intermediate layer. Compared with the prior art, the hydrotalcite solution is used as a secondary intermediate layer, and is combined with polyurethane / polyimide and red phosphorus / graphene aerogel respectively through the groups thereon, thereby avoiding the problem of clogging the pores of the aerogel, and at the same time enhancing the overall performance of the material and improving the thermal insulation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0029] like Figure 1 As shown, a method for preparing an ultra-thin buffer insulation sheet based on polyimide foam material comprises the following steps:
[0030] S1: The polyimide polyol raw material is mixed with the polyurethane solution and melt-treated to obtain a polyurethane / polyimide composite raw material; the composite of polyimide and polyurethane is achieved through mixing and melt-treatment, which combines the high strength and high temperature resistance of polyimide with the flexibility and good processability of polyurethane, providing a raw material with superior performance for the subsequent preparation of thermal insulation sheets.
[0031] S2: Mix red phosphorus and graphene oxide solution and heat them, freeze-dry the resulting mixed solution to obtain red phosphorus / graphene aerogel; red phosphorus, as a flame retardant, can improve the flame retardant properties of the material; while graphene oxide, due to its excellent mechanical properties and thermal conductivity, helps to improve the overall performance of the material. The red phosphorus / graphene aerogel obtained by freeze-drying technology maintains a porous structure, which is conducive to further improving the thermal insulation and flame retardant properties.
[0032] S3: Magnesium aluminum hydrotalcite powder is placed in a glycine solution, soaked for 1-2 hours, and then taken out and dried to obtain substituted magnesium aluminum hydrotalcite powder. The substituted magnesium aluminum hydrotalcite powder and a silane coupling agent are added to 75% ethanol and mixed to obtain a hydrotalcite solution; magnesium aluminum hydrotalcite has good flame retardant and filling properties. The soaking and replacement treatment in the glycine solution and the subsequent silane coupling agent treatment help improve its dispersibility and bonding ability with the substrate. The formation of the hydrotalcite solution provides bonding conditions for the subsequent bonding with red phosphorus / graphene aerogel and polyurethane / polyimide composite materials and can reduce the blockage of pores.
[0033] S4: The red phosphorus / graphene aerogel in S2 is used as an intermediate layer, the hydrotalcite solution in S3 is coated on the red phosphorus / graphene aerogel and dried to form a secondary intermediate layer, the polyurethane / polyimide composite material is placed on the secondary intermediate layer by ultrasonic spraying, and after drying, an ultra-thin buffer insulation sheet based on polyimide foam material is obtained. By combining the red phosphorus / graphene aerogel, the hydrotalcite solution and the polyurethane / polyimide composite material, a composite insulation layer is formed, and this structure helps to improve the insulation effect.
[0034] Through the clever stacking structure, the organic combination of red phosphorus / graphene aerogel, hydrotalcite solution and polyurethane / polyimide composite raw materials is achieved. Red phosphorus / graphene aerogel as the middle layer provides excellent flame retardant and heat insulation properties; hydrotalcite solution as the secondary middle layer is combined with polyurethane / polyimide and red phosphorus / graphene aerogel through the groups on it, avoiding the problem of blocking the pores of the aerogel and enhancing the overall performance of the material; polyurethane / polyimide composite raw materials as the outermost layer provide good processability and strength. The entire structure improves the heat insulation effect while maintaining the lightness and strength of the material.
[0035] A polyimide polyol raw material is mixed with a polyurethane solution to prepare a polyurethane / polyimide composite raw material, red phosphorus is mixed with a graphene oxide solution, heated and then freeze-dried to prepare a red phosphorus / graphene aerogel, magnesium aluminum hydrotalcite powder is placed in a glycine solution for replacement to prepare a hydrotalcite solution, and the red phosphorus / graphene aerogel, the hydrotalcite solution and the polyurethane / polyimide composite raw material are sequentially combined together to prepare a thermal insulation sheet, which can be combined with polyurethane / polyimide and red phosphorus / graphene aerogel respectively through groups on the hydrotalcite while avoiding affecting the pore structures of the two, and can be connected with polyurethane / polyimide and red phosphorus / graphene aerogel respectively through chemical bond connection to avoid entering the pores of the aerogel and blocking the aerogel, thereby solving the defect of reduced thermal insulation performance of the combined material caused by combining polyimide with aerogel materials in the prior art.
[0036] The solid content of the polyurethane solution in S1 is 30%-50%, and the isocyanate index in the polyurethane solution is 1.05-1.15. Adjusting the isocyanate index can increase the hardness of polyurethane at the same density. Within this range, the increase in the isocyanate index will lead to an increase in the hardness of the foam, which helps to improve the hardness and strength of the material.
[0037] The mass ratio of the polyimide polyol raw material to the polyurethane solution in S1 is 1:1.5-2.0, the melting temperature is 120-150°C, and the melting time is 30-60 minutes. By precisely controlling the mass ratio of the polyimide polyol raw material to the polyurethane solution, it is possible to ensure that the two react fully to form a uniform polyurethane / polyimide composite raw material. This ratio setting helps to balance the mechanical properties and thermal stability of the material and improve the overall performance of the composite material.
[0038] The concentration of graphene oxide solution in S2 is 2-5 mg / mL, and the mass ratio of red phosphorus to graphene oxide solution is 1:5-10. The temperature of mixing and heating red phosphorus and graphene oxide solution in S2 is 80-100°C, the mixing and heating time is 30 minutes, and the freeze-drying process is: freezing at -50°C for 24-28 hours and then vacuum drying for 48-50 hours. It helps to form a uniform aerogel structure, avoid pore blockage caused by excessive concentration, and form uniformly dispersed red phosphorus / graphene aerogel to avoid destruction of the pore structure. It is conducive to the interaction between red phosphorus and graphene oxide, forming a stable aerogel structure, while avoiding the destruction of the aerogel structure caused by excessive temperature, thereby maintaining good thermal insulation properties. The freeze-drying method helps to maintain the porous structure of the aerogel, avoids the collapse and blockage of the pores, thereby maintaining the low thermal conductivity and excellent thermal insulation properties of the aerogel.
[0039] The mass fraction of magnesium in the magnesium-aluminum hydrotalcite powder in S3 is 30-35%, the mass fraction of aluminum is 35-40%, the particle size of the magnesium-aluminum hydrotalcite powder is 5-20μm, the concentration of the glycine solution is 1-2mol / L, the immersion time is 1-2h, and the silane coupling agent is one of KH-550 and KH-560. The particle size of the magnesium-aluminum hydrotalcite powder is 5-20μm, and this particle size range helps to maintain the pore structure of the aerogel and avoid pore clogging by excessively large particles. The concentration of the glycine solution is 1-2mol / L, and the appropriate concentration helps the uniform replacement of the magnesium-aluminum hydrotalcite powder without excessively affecting the pore structure. The application of silane coupling agents KH-550 and KH-560 can improve the wettability and dispersibility of inorganic fillers in polymers, reduce agglomeration, and thus avoid pore clogging.
[0040] The drying condition in S3 is drying at 60-80°C for 4-6h, and the mass ratio of the magnesium aluminum hydrotalcite powder, the silane coupling agent and 75% ethanol is 1:0.05-0.1:10-20. Such a mass ratio helps to form a stable hydrotalcite structure and improve the thermal insulation performance of the material. When the magnesium aluminum hydrotalcite powder is thermally decomposed, it can absorb heat, release water and carbon dioxide, reduce the temperature of the combustion system, and thus improve the thermal insulation effect.
[0041] The ultrasonic spraying frequency in S4 is 20-40kHz, and the drying condition of the polyurethane / polyimide composite raw material is drying at 80-100℃ for 4-8h. Ultrasonic spraying technology atomizes the liquid into uniform droplets of micron size through high-frequency sound waves, which helps to maintain the integrity of the aerogel pore structure and avoids pore blockage caused by large particles or droplets generated during the spraying process. The coating can act as a barrier to reduce heat conduction and heat convection. Uniform coating helps to reduce heat transfer. The polyurethane / polyimide composite material itself has good thermal insulation properties, and this effect can be further enhanced by uniform coating.
[0042] The mass ratio of the polyurethane / polyimide composite raw material, the hydrotalcite solution and the red phosphorus / graphene aerogel in S4 is 1:0.75-1.25:1.5-2. By controlling the mass ratio of the polyurethane / polyimide composite raw material and the hydrotalcite solution, it is possible to avoid excessive material deposition in the pores of the red phosphorus / graphene aerogel, thereby maintaining the porous structure of the aerogel. This helps to avoid overfilling, maintain the pore structure of the aerogel, thereby maintaining its excellent thermal insulation performance, and avoid the destruction of the pore structure caused by overfilling.
[0043] In order to achieve the above-mentioned purpose, the second technical solution adopted by the present invention is: an application of an ultra-thin buffer insulation sheet based on polyimide foam material, and the ultra-thin buffer insulation sheet is used to prepare a battery insulation sheet.
[0044] Embodiment 1
[0045] S1: Mix the polyimide polyol raw material and the polyurethane solution and melt-treat them to obtain a composite raw material. The solid content of the polyurethane solution is 40%, and the isocyanate index is 1.1. The mass ratio of the polyimide polyol raw material to the polyurethane solution is 1:2, the melting temperature is 120°C, and the time is 60 minutes.
[0046] S2: Red phosphorus and graphene oxide solution were mixed, heated, and freeze-dried to obtain aerogel. The concentration of graphene oxide solution was 3 mg / mL, and the mass ratio of red phosphorus to graphene oxide solution was 1:2.5. The heating temperature was 80°C for 30 minutes, and freeze-dried at -50°C for 28 hours, followed by vacuum drying for 48 hours.
[0047] S3: Magnesium aluminum hydrotalcite powder is placed in glycine solution for replacement to form hydrotalcite solution. The mass fraction of magnesium in magnesium aluminum hydrotalcite powder is 35%, the mass fraction of aluminum is 40%, the particle size is 5μm, the concentration of glycine solution is 1mol / L, and the immersion time is 2 hours. The silane coupling agent is KH-550, the drying condition is 80℃ for 4 hours, and the mass ratio is 1:0.05:10.
[0048] S4: Red phosphorus / graphene aerogel is used as an intermediate layer, and a hydrotalcite solution is coated and dried to form a secondary intermediate layer. The polyurethane / polyimide composite material is placed on the secondary intermediate layer by ultrasonic spraying, and a heat insulation sheet is obtained after drying. The mass ratio between the polyurethane / polyimide composite material, the hydrotalcite solution and the red phosphorus / graphene aerogel is 1:0.5:2. The ultrasonic spraying frequency is 40kHz, and the drying condition of the polyurethane / polyimide composite material is dried at 100°C for 8 hours.
[0049] Embodiment 2
[0050] S1: Mix the polyimide polyol raw material and the polyurethane solution and melt-treat them to obtain a composite raw material. The solid content of the polyurethane solution is 40%, and the isocyanate index is 1.1. The mass ratio of the polyimide polyol raw material to the polyurethane solution is 1:2, the melting temperature is 120°C, and the time is 60 minutes.
[0051] S2: Red phosphorus and graphene oxide solution were mixed, heated, and freeze-dried to obtain aerogel. The concentration of graphene oxide solution was 3 mg / mL, and the mass ratio of red phosphorus to graphene oxide solution was 1:2.5. The heating temperature was 80°C for 30 minutes, and freeze-dried at -50°C for 28 hours, followed by vacuum drying for 48 hours.
[0052] S3: Magnesium aluminum hydrotalcite powder is placed in glycine solution for replacement to form hydrotalcite solution. The mass fraction of magnesium in magnesium aluminum hydrotalcite powder is 35%, the mass fraction of aluminum is 40%, the particle size is 5μm, the concentration of glycine solution is 1mol / L, and the immersion time is 2 hours. The silane coupling agent is KH-550, the drying condition is 80℃ for 4 hours, and the mass ratio is 1:0.05:10.
[0053] S4: Red phosphorus / graphene aerogel is used as an intermediate layer, and a hydrotalcite solution is coated and dried to form a secondary intermediate layer. The polyurethane / polyimide composite material is placed on the secondary intermediate layer by ultrasonic spraying, and a heat insulation sheet is obtained after drying. The mass ratio between the polyurethane / polyimide composite material, the hydrotalcite solution and the red phosphorus / graphene aerogel is 1:0.75:2. The ultrasonic spraying frequency is 40kHz, and the drying condition of the polyurethane / polyimide composite material is dried at 100°C for 8 hours.
[0054] Embodiment 3
[0055] S1: Mix the polyimide polyol raw material and the polyurethane solution and melt-treat them to obtain a composite raw material. The solid content of the polyurethane solution is 40%, and the isocyanate index is 1.1. The mass ratio of the polyimide polyol raw material to the polyurethane solution is 1:2, the melting temperature is 120°C, and the time is 60 minutes.
[0056] S2: Red phosphorus and graphene oxide solution were mixed, heated, and freeze-dried to obtain aerogel. The concentration of graphene oxide solution was 3 mg / mL, and the mass ratio of red phosphorus to graphene oxide solution was 1:2.5. The heating temperature was 80°C for 30 minutes, and freeze-dried at -50°C for 28 hours, followed by vacuum drying for 48 hours.
[0057] S3: Magnesium aluminum hydrotalcite powder is placed in glycine solution for replacement to form hydrotalcite solution. The mass fraction of magnesium in magnesium aluminum hydrotalcite powder is 35%, the mass fraction of aluminum is 40%, the particle size is 5μm, the concentration of glycine solution is 1mol / L, and the immersion time is 2 hours. The silane coupling agent is KH-550, the drying condition is 80℃ for 4 hours, and the mass ratio is 1:0.05:10.
[0058] S4: Red phosphorus / graphene aerogel is used as an intermediate layer, and a hydrotalcite solution is coated and dried to form a secondary intermediate layer. The polyurethane / polyimide composite material is placed on the secondary intermediate layer using ultrasonic spraying, and a heat insulation sheet is obtained after drying. The mass ratio between the polyurethane / polyimide composite material, the hydrotalcite solution and the red phosphorus / graphene aerogel is 1:1:2. The ultrasonic spraying frequency is 40kHz, and the drying condition of the polyurethane / polyimide composite material is dried at 100°C for 8 hours.
[0059] Embodiment 4
[0060] S1: Mix the polyimide polyol raw material and the polyurethane solution and melt-treat them to obtain a composite raw material. The solid content of the polyurethane solution is 40%, and the isocyanate index is 1.1. The mass ratio of the polyimide polyol raw material to the polyurethane solution is 1:2, the melting temperature is 120°C, and the time is 60 minutes.
[0061] S2: Red phosphorus and graphene oxide solution were mixed, heated, and freeze-dried to obtain aerogel. The concentration of graphene oxide solution was 3 mg / mL, and the mass ratio of red phosphorus to graphene oxide solution was 1:2.5. The heating temperature was 80°C for 30 minutes, and freeze-dried at -50°C for 28 hours, followed by vacuum drying for 48 hours.
[0062] S3: Magnesium aluminum hydrotalcite powder is placed in glycine solution for replacement to form hydrotalcite solution. The mass fraction of magnesium in magnesium aluminum hydrotalcite powder is 35%, the mass fraction of aluminum is 40%, the particle size is 5μm, the concentration of glycine solution is 1mol / L, and the immersion time is 2 hours. The silane coupling agent is KH-550, the drying condition is 80℃ for 4 hours, and the mass ratio is 1:0.05:10.
[0063] S4: Red phosphorus / graphene aerogel is used as an intermediate layer, and a hydrotalcite solution is coated and dried to form a secondary intermediate layer. The polyurethane / polyimide composite material is placed on the secondary intermediate layer by ultrasonic spraying, and a heat insulation sheet is obtained after drying. The mass ratio between the polyurethane / polyimide composite material, the hydrotalcite solution and the red phosphorus / graphene aerogel is 1:1.25:2. The ultrasonic spraying frequency is 40kHz, and the drying condition of the polyurethane / polyimide composite material is dried at 100°C for 8 hours.
[0064] Embodiment 5
[0065] S1: Mix the polyimide polyol raw material and the polyurethane solution and melt-treat them to obtain a composite raw material. The solid content of the polyurethane solution is 40%, and the isocyanate index is 1.1. The mass ratio of the polyimide polyol raw material to the polyurethane solution is 1:2, the melting temperature is 120°C, and the time is 60 minutes.
[0066] S2: Red phosphorus and graphene oxide solution were mixed, heated, and freeze-dried to obtain aerogel. The concentration of graphene oxide solution was 3 mg / mL, and the mass ratio of red phosphorus to graphene oxide solution was 1:2.5. The heating temperature was 80°C for 30 minutes, and freeze-dried at -50°C for 28 hours, followed by vacuum drying for 48 hours.
[0067] S3: Magnesium aluminum hydrotalcite powder is placed in glycine solution for replacement to form hydrotalcite solution. The mass fraction of magnesium in magnesium aluminum hydrotalcite powder is 35%, the mass fraction of aluminum is 40%, the particle size is 5μm, the concentration of glycine solution is 1mol / L, and the immersion time is 2 hours. The silane coupling agent is KH-550, the drying condition is 80℃ for 4 hours, and the mass ratio is 1:0.05:10.
[0068] S4: Red phosphorus / graphene aerogel is used as an intermediate layer, and a hydrotalcite solution is coated and dried to form a secondary intermediate layer. The polyurethane / polyimide composite material is placed on the secondary intermediate layer using ultrasonic spraying, and a heat insulation sheet is obtained after drying. The mass ratio between the polyurethane / polyimide composite material, the hydrotalcite solution and the red phosphorus / graphene aerogel is 1:1.5:2. The ultrasonic spraying frequency is 40kHz, and the drying condition of the polyurethane / polyimide composite material is dried at 100°C for 8 hours.
[0069] Comparative Example 1
[0070] S1: Red phosphorus and graphene oxide solution were mixed, heated, and freeze-dried to obtain aerogel. The concentration of graphene oxide solution was 3 mg / mL, and the mass ratio of red phosphorus to graphene oxide solution was 1:2.5. The heating temperature was 80°C for 30 minutes, and freeze-dried at -50°C for 28 hours, followed by vacuum drying for 48 hours.
[0071] S2: Red phosphorus / graphene aerogel is used as an intermediate layer, polyimide is sprayed on the intermediate layer, and a heat insulation sheet is obtained after drying. The mass ratio between polyimide and red phosphorus / graphene aerogel is 1:2. The drying condition of polyimide is 100°C for 8 hours.
[0072] Samples of equal mass were taken from Examples 1 to 5 and Comparative Example 1, and the thermal conductivity of the samples was measured according to the standard ISO22007-2-2008. The measured data are shown in Table 1.
[0073] Table 1 Thermal conductivity data of Examples 1 to 5 and Comparative Example 1
[0074] Sample source <![CDATA[Thermal conductivity (W·m -1 ·K -1 )]]> Embodiment 1 0.0261 Embodiment 2 0.0223 Embodiment 3 0.0206 Embodiment 4 0.0229 Embodiment 5 0.0258 Comparative Example 1 0.0355
[0075] It can be seen from Table 1 that the thermal conductivity coefficients in Examples 1 to 5 are all lower than that in Comparative Example 1. The lower the thermal conductivity coefficient, the better the thermal insulation capacity. This application is superior.
[0076] In Examples 1 to 5, as the mass proportion of the hydrotalcite solution in the thermal insulation sheet gradually increases, the mass proportion of the secondary intermediate layer in the thermal conductive sheet increases, and the thermal conductivity first decreases and then increases. This is because when the mass proportion of the hydrotalcite solution increases, it may form more micropores or gaps in the thermal conductive sheet, and these micropores or gaps can act as obstacles to heat conduction, thereby reducing the thermal conductivity; as the mass proportion of the hydrotalcite solution is too high, the thermal conductive sheet becomes more dense, and densification will enhance the thermal conductivity of the material, thereby improving the thermal conductivity. The preferred embodiment is Example 3.
[0077] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing an ultra-thin buffer insulation sheet based on polyimide foam material, characterized in that: The following steps are involved: S1: mixing a polyimide polyol raw material with a polyurethane solution, and performing a melt treatment to obtain a polyurethane / polyimide composite raw material; S2: mixing red phosphorus and graphene oxide solution and heating them, and freeze-drying the obtained mixed solution to obtain red phosphorus / graphene aerogel; S3: placing magnesium aluminum hydrotalcite powder in a glycine solution, soaking for 1-2 hours, taking out and drying to obtain substituted magnesium aluminum hydrotalcite powder, adding the substituted magnesium aluminum hydrotalcite powder and a silane coupling agent into 75% ethanol and mixing to obtain a hydrotalcite solution; S4: The red phosphorus / graphene aerogel in S2 is used as an intermediate layer, the hydrotalcite solution in S3 is coated on the red phosphorus / graphene aerogel and dried to form a secondary intermediate layer, the polyurethane / polyimide composite material is placed on the secondary intermediate layer by ultrasonic spraying, and after drying, an ultra-thin buffer insulation sheet based on polyimide foam material is obtained.
2. The method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to claim 1, characterized in that: The solid content of the polyurethane solution in S1 is 30%-50%, and the isocyanate index of the polyurethane solution is 1.05-1.
15.
3. The method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to claim 1, characterized in that: The mass ratio of the polyimide polyol raw material to the polyurethane solution in S1 is 1:1.5-2.0, the melting treatment temperature is 120-150° C., and the melting treatment time is 30-60 min.
4. The method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to claim 1, characterized in that: The concentration of the graphene oxide solution in S2 is 2-5 mg / mL, and the mass ratio of the red phosphorus to the graphene oxide solution is 1:5-10.
5. The method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to claim 1, characterized in that: The temperature for mixing and heating the red phosphorus and the graphene oxide solution in S2 is 80-100° C., the mixing and heating time is 30 min, and the freeze-drying process is: freezing at -50° C. for 24-28 h and then vacuum drying for 48-50 h.
6. The method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to claim 1, characterized in that: The mass fraction of magnesium in the magnesium-aluminum hydrotalcite powder in S3 is 30-35%, the mass fraction of aluminum is 35-40%, the particle size of the magnesium-aluminum hydrotalcite powder is 5-20 μm, the concentration of the glycine solution is 1-2 mol / L, the immersion time is 1-2 h, and the silane coupling agent is one of KH-550 and KH-560.
7. The method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to claim 1, characterized in that: The drying condition in S3 is drying at 60-80° C. for 4-6 hours, and the mass ratio of the substituted magnesium aluminum hydrotalcite powder, the silane coupling agent and the 75% ethanol is 1:0.05-0.1:10-20.
8. The method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to claim 1, characterized in that: The ultrasonic spraying frequency in S4 is 20-40 kHz, and the drying condition of the polyurethane / polyimide composite raw material is drying at 80-100° C. for 4-8 hours.
9. The method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to claim 1, characterized in that: The mass ratio of the polyurethane / polyimide composite material, the hydrotalcite solution and the red phosphorus / graphene aerogel in S4 is 1:0.75-1.25:1.5-2.
10. An application of an ultra-thin buffer thermal insulation sheet based on polyimide foam material, a method for preparing an ultra-thin buffer thermal insulation sheet based on polyimide foam material according to any one of claims 1 to 9, characterized in that: The ultra-thin buffer thermal insulation sheet is used for preparing a battery thermal insulation sheet.